Improving Vocational School Students' Skills in Land Surveying with Team-Based Projects Using Augmented Reality - Setiawan, Abdul Haris; Agustin, Rima Sri; Murtiono, Eko Supri; Trianingsih, Lilis; Mitsuhara, Hiroyuki (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2024)
This research aims to determine the increase in land surveying competency of Civil Engineering Vocational School students through team-based project strategies and augmented reality learning media. This research is vital because land surveying competency is critical for Civil Engineering Vocational School students in facing the demands of the ever-growing construction industry. This research uses two different classes of data: class A (35 students) as the experiment and class B (36 students) as the control class. Data analysis was done using descriptive statistical methods and independent samples t-test. The results showed that the survey competency score for class A increased from 53.57 (pre-test) to 85.36 (post-test) on a scale 100. Meanwhile, the competency score for class B increased from 53.89 (pre-test) to 72.22 (post-test). An N-gain score of 0.6962 shows an increase in competency of 69.62%. The independent sample t-test shows that the pre-test for both classes is the same with a t-count of 0.104 < t-table = 1.997 and a Sig. (2-tailed) 0.917 > probability 0.05. The post-test results show that there is a significant difference between class A (experimental class) and class B (control class) with a calculated t-value of 8.649 > t-table = 1.997 and a Sig. (2-tailed) 0.000 < 0.05. In conclusion, team-based project strategies and augmented reality learning media significantly increase students' land surveying competency. The implications of this research indicate that the application of augmented reality technology in civil engineering learning can effectively increase student competency. Future research recommendations are to explore the use of augmented reality in other engineering fields and evaluate its impact on students' practical competencies. The research can also be expanded to involve more schools and classes to strengthen these findings.